A new fossil accipitrid (aves, accipitriformes) from the pliocene of the eastern puna, Jujuy province, Argentina - Degrange, Federico Javier; Barasoain Goñi, Daniel; Quiñones, Sofía Inés; Miño Boilini, Ángel Ramón; Luna, Carlos Alberto; Cuadrelli, Francisco; Cuaranta, Pedro; Contreras, Silvina Andrea; Candela, A. M.; Zurita, Alfredo Eduardo
Accipitriformes is a group of powerful diurnal predatory birds, living in most habitats across all continents (except Antarctica), including a large disparity of taxa such as buzzards, hawks, kites, Old-world vultures, eagles, osprey and the secretary bird. Although the fossil record of Accipitriformes starts in the early-middle Paleogene, its record is extremely scarce in South America. The oldest records are registered in the Oligocene, but the main findings come from Mio-Pliocene sediments. Here we present the first avian remains coming from the upper member of the Tafna Formation (Pliocene) of Casira locality, eastern Puna, Jujuy Province, Argentina. The new specimen corresponds to a large Accipitridae, represented by a fairly complete skeleton that includes a partial skull and pectoral girdle, complete forelimbs, vertebrae, and incomplete pelvis and hind limbs. The fossil shows similarities with the extant Black-chested Buzzard-Eagle Geranoaetus melanoleucus, mainly on the forelimb and pectoral girdle morphology, being notoriously sturdier and ~10% larger, and quite similar in size to the extant Chaco Eagle Buteogallus coronatus, and Vinchinavis paka from the late Miocene of Quebrada de la Troya (La Rioja Province), but ~8% smaller than Buteo dondasi from the late Pliocene of Chapadmalal Formation (Buenos Aires Province). Eagles inhabit very different environments, and their presence suggests the abundance of available prey as a biomass source. The new fossil adds new evidence to the knowledge of fossil Eagles disparity (especially for those from the Pliocene), but also highlights the presence of larger sizes achieved by these taxa at this epoch. Fil: Degrange, Federico Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Barasoain Goñi, ...